Hubungan Pengetahuan Dengan Tindakan Swamedikasi Batuk Di Apotek Perintis Tegal - Safitri, Maya Diki; Sari, Meliyana Perwita; Barlian, Akhmad Aniq (LPPM Akafarma Sunan Giri Ponorogo, 2024)
Abstract Be under the supervision of pharmacists since it is a human habit that individuals often engage in to find answers to health-related issues. take appropriate action when self-medicating, people need relevant information. As an external disturbance, cough is the body's natural defense mechanism to maintain airway integrity. The purpose of this study was to determine the relationship between knowledge and behavior of cough self-medication at Perintis Tegal Pharmacy. This study used a cross-sectional approach methodology and was descriptive and quantitative in nature. Quota sampling was used as the sample method. There were 110 respondents in the sample. The research was conducted in August and September 2023. Using SPSS version 22, a direct linear regression analysis model was used for data analysis. As an external disturbance, cough is the body's natural defense mechanism to maintain airway integrity. The purpose of this study was to determine the relationship between knowledge and behavior of cough self-medication at Perintis Tegal Pharmacy. This study used a cross-sectional approach methodology and was descriptive and quantitative in nature. Quota sampling was used as the sample method. There were 110 respondents in the sample. The research was conducted in August and September 2023. By using SPSS version 22, a direct linear regression analysis model was used to analyze the results.Keywords: Cough, Self-medication, Knowledge, Action, Perintis Pharmacy.